Do latex and resin canals spur plant diversification? Re‐examining a classic example of escape and radiate coevolution. (10th June 2019) - Foisy, Michael R.; Albert, Loren P.; Hughes, Daniel W. W.; Weber, Marjorie G.
Abstract: The association between increased lineage diversification rates and the evolution of latex and resin canals is widely cited as a paradigmatic example of Ehrlich and Raven's 'escape‐and‐radiate' hypothesis of co‐evolution. However, it has been over a quarter‐century since the original study, and updates to phylogenetic comparative methods, plant molecular systematics, and phenotypic data warrant a reassessment of this classic finding. We gathered data on latex and resin canals across 345 families and 986 genera of vascular plants and conducted a multi‐scale test of the association between these traits and lineage diversification rates. At a broad scale (across clades), we used sister‐clade comparisons to test whether 28 canal‐bearing clades had higher net diversification rates than their canal‐lacking sister clades. At a finer scale (within clades), we used ancestral state reconstructions and phylogenetic models of lineage diversification rates to examine the relationship between trait evolution and the timing of diversification rate shifts in two better‐characterized clades – Araceae and Papaveraceae. At both scales of our analyses we found poor support for the predicted relationship between diversification and the evolution of latex and resin canals. Follow‐up analyses clarified that the qualitative change between our results and those of the Farrell et al.'s classic study is not the result of different phylogenetic comparative methods. Instead, the differences are attributable to updates to plant systematic hypotheses and new data on laticifers and resin canal presence/absence. Synthesis. Our updated study reveals that there is no longer strong evidence for latex or resin canals as general, consistently replicable drivers of species diversity across plants. However, we cannot rule out a relationship in all groups. We therefore argue that theoretical and empirical work aimed at understanding ecological factors that condition 'escape‐and‐radiate' dynamics will allow for more nuanced tests of the hypothesis in the future. Abstract : Rich latex exuded by Papaver somniferum (Papaveraceae), near Chihuahua, Mexico (photo credit: Anurag Agrawal). This sticky "goo" helps plants defend against insect herbivores, and is thought to have driven the diversification on plant species.